Enhanced adsorption of tetracycline by an iron and manganese oxides loaded biochar: Kinetics, mechanism and column adsorption - Zhang, Xin; Li, Yaru; Wu, Mengru; Pang, Yao; Hao, Zhenbing; Hu, Mian; Qiu, Rongliang; Chen, Zhihua (Bioresource technology, 2021)
[Display omitted] •Fe/Mn oxides loaded biochar could enhance the adsorption of tetracycline.•γ-Fe2O3 and MnO2 were the main crystalline phases of Fe/Mn oxides.•Fe/Mn oxides play complex acid and base roles to enhance the tetracycline adsorption.•Adsorption of tetracycline follow Elovich kinetic model and Langmuir isotherm. A Fe/Mn oxides loaded biochar (FeMn-BC) was prepared to enhance the adsorption of tetracycline (TC). γ-Fe2O3 and MnO2 were assigned to the Fe and Mn oxides, respectively. The enhanced adsorption of TC was dominated by the loaded γ-Fe2O3 and MnO2. According to Akaike-Information-Criteria evaluation, Elovich kinetic and Langmuir isotherm models could best describe the adsorption with a maximum capacity of 14.24 mg/g. During adsorption process, the γ-Fe2O3 and MnO2 hydrolyzed into hydroxides (FeOOH and MnOOH) which acted as bases to complex with TC2− ion under alkaline condition (pH = 11). After the adsorption, the concentrations of leached Fe and Mn could meet the requirements PRC standards GB13456-2012 and GB8978-1996, respectively. The FeMn-BC had ~24% on TC removal (initial concentration of 20 mg/L) after four-cycles regeneration. The FeMn-BC was also available for TC adsorptions in column tests and actual wastewater.